2009
DOI: 10.1002/j.2051-5545.2009.tb00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Indexation of psychiatric journals from low‐ and middle‐income countries: a survey and a case study

Abstract: There is a marked underepresentation of low-and middle-income countries (LAMIC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, dissemination of this work to national and international audiences is hampered by the poor representation of publications from LAMIC in mainstream psychiatric journals 23,24. Recent work by WPA has demonstrated that, despite a significant level of scientific activity shown by China (as well as India, South Africa and South Korea), none of these countries, and indeed, no LAMIC in the African and Asian regions, is so far represented by a psychiatric journal in the main international databases 25,26. Internationally supported action to improve indexation of journals and research dissemination will aid the publication of data from this and similar projects.…”
Section: Chinese Experiences As Response To International Advocacymentioning
confidence: 99%
“…However, dissemination of this work to national and international audiences is hampered by the poor representation of publications from LAMIC in mainstream psychiatric journals 23,24. Recent work by WPA has demonstrated that, despite a significant level of scientific activity shown by China (as well as India, South Africa and South Korea), none of these countries, and indeed, no LAMIC in the African and Asian regions, is so far represented by a psychiatric journal in the main international databases 25,26. Internationally supported action to improve indexation of journals and research dissemination will aid the publication of data from this and similar projects.…”
Section: Chinese Experiences As Response To International Advocacymentioning
confidence: 99%
“…The WPA has implemented during the triennium an initiative to support the development of national psychiatric journals in low‐ and middle‐income countries. A task force has worked with editors of selected journals to strengthen their chances of being indexed in international databases 36. Several journals whose editors participated in this project have recently achieved indexation.…”
Section: Other Activities In Partnership With Member Societiesmentioning
confidence: 99%